Biliary Anastomotic Stricture After Adult Living Donor Liver Transplantation With Duct-to-Duct Reconstruction: Outcome After Endoscopic Treatment Including Rendezvous Procedure. Issue 7 (July 2016) - Tomoda, Takeshi; Kato, Hironari; Mizukawa, Sho; Yabe, Syuntaro; Akimoto, Yutaka; Seki, Hiroyuki; Uchida, Daisuke; Matsumoto, Kazuyuki; Yamamoto, Naoki; Horiguchi, Shigeru; Tsutsumi, Koichiro; Okada, Hiroyuki
Abstract : Background: To evaluate the outcomes and investigate the factors associated with restricture after endoscopic treatment. Methods: Between April 2001 and July 2014, 98 patients experienced biliary anastomotic stricture (BAS) after living donor liver transplantation (LDLT) with duct-to-duct reconstruction, and all were first referred to Okayama University Hospital for endoscopic stent deployment. When deployment was unsuccessful, a percutaneous transhepatic procedure was used. Treatment outcomes, including stricture resolution, BAS recurrence, and risk factors of BAS recurrence, were evaluated retrospectively. Results: Successful stent deployment was achieved in 90 of 98 patients (91.8%) by both procedures. Among the 90 patients, stricture resolution was eventually observed in 72. The median number of endoscopic retrograde cholangiographies performed was 5. After a median follow-up period of 48.8 months from stent removal, BAS recurrence that required intervention occurred in 22 patients (30.6%). In multivariate analysis, portal vein stenosis after LDLT was associated with BAS recurrence after endoscopic treatment ( P = 0.03). Among the 22 patients who required reintervention, 16 (73%) had their stents removed, and recurrence after retreatment occurred in 3 patients (18.8%). Conclusions: Endoscopic treatment is a useful procedure for the treatment for BAS after LDLT with duct-to-duct reconstruction. Portal vein stenosis may be one of the risks associated with the recurrence of BAS. Abstract : This report from Tomoda et al documents interventional endoscopic management of 98 patients with biliary strictures after LDLT with successful treatment in 73% of patients. Detailed description of technique and results are presented.